2022
DOI: 10.1002/adfm.202203418
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Plasmonic Bimetallic Nanocatalysts Toward Sunlight‐Driven H2 Production

Abstract: Hybrid nanoparticles combining plasmonic and catalytic components have recently gained interest for their potential use in sunlight‐to‐chemical energy conversion. However, a deep understanding of the structure–performance that maximizes the use of the incoming energy remains elusive. Here, a suite of Au and Pd based nanostructures in core–shell and core‐satellites configurations are designed and their photocatalytic activity for Hydrogen (H2) generation under sunlight illumination is tested. Formic acid is emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 85 publications
(119 reference statements)
0
51
0
Order By: Relevance
“…153 In another report, Herran et al observed enhanced FA dehydrogenation performance over Au-Pd core−satellite structures in comparison with Au-Pd core−shell structures (Figure 12b). 156 Moreover, introducing AuPd alloy as the satellite further enhanced the photocatalytic performance for H 2 production (191 mmol g Pd −1 h −1 ). Based on the electromagnetic simulations, it was proposed that the Au plasmon-induced intense LEMF promoted the electron transition in Pd.…”
Section: Active Site-engineered Plasmonic Nanostructures For Emerging...mentioning
confidence: 99%
See 1 more Smart Citation
“…153 In another report, Herran et al observed enhanced FA dehydrogenation performance over Au-Pd core−satellite structures in comparison with Au-Pd core−shell structures (Figure 12b). 156 Moreover, introducing AuPd alloy as the satellite further enhanced the photocatalytic performance for H 2 production (191 mmol g Pd −1 h −1 ). Based on the electromagnetic simulations, it was proposed that the Au plasmon-induced intense LEMF promoted the electron transition in Pd.…”
Section: Active Site-engineered Plasmonic Nanostructures For Emerging...mentioning
confidence: 99%
“…Moreover, by introducing 5-bromosalicylic acid as a cosurfactant, the preferential deposition of Pd at the tips of Au nanorods (i.e., site-selective deposition) was achieved, forming Pd-tipped Au nanorods (Figure d) . Following the template-assisted synthetic strategy, plasmonic AuPd hybrids with different configurations, such as Au nanorod@Pd superstructures, Au@Pd core-ultrathin shell nanorods, and Au@Pd core–satellite nanoparticles (formed by the colloidal assemble of Au core and Pd satellites), have been successfully prepared. In addition, it is worth noting that similar lattice constants (with a difference of < 5%) between plasmonic metal and metallic sites are considered a basic requirement for the preparation of core–shell nanostructures with a continuous shell layer .…”
Section: Preparation and Characterization Of Active Site-engineered P...mentioning
confidence: 99%
“…11 All these processes can contribute to promoting or enhancing photocatalytic reactions at the surface of resonantly illuminated MNPs. [12][13][14] Plasmonic catalysis has been recently used in sunlight-to-chemical energy conversion for solar fuel production (H 2 generation and CO 2 reduction), 15,16 plasmon-assisted chemistry of organic compounds, [17][18][19] hot-carrier-driven redox reactions, [20][21][22] and degradation of environmental pollutants. 23,24 However, there are far fewer examples of the reduction of inorganic ions such as arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 One very effective strategy is incorporation of plasmonic metal nanoparticles. 21–24 The pairing of plasmonic metal nanoparticles with semiconductors has a long history that can date back to early 70s. Since plasmonic metal nanoparticles usually possess larger work functions than semiconductors, they could extract photogenerated electrons from semiconductors when they are in direct contact to enable efficient separation of electron–hole pairs.…”
Section: Introductionmentioning
confidence: 99%